PENERAPAN METODE EKSPERIMEN DALAM PEMBELAJARAN IPA DI SDN INPRES BUMI BAHARI - Haeroni Haeroni; Thalib Thalib; Karmawati Karmawati (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
This research discusses "The Application of Experimental Methods in Science Learning in SDN Inpres Bumi Bahari." By raising the issue: 1. How is the application of experimental methods in learning science in SDN Inpres Bumi Bahari? 2. What are the obstacles to the application of experimental methods in learning science in SDN Inpres Bumi Bahari, and how is the solution to overcome the application of experimental methods in learning science in SDN Inpres Bumi Bahari?. The research used is qualitative research. This study uses data collection techniques through observation, interviews, and documentation. While the data analysis technique used is data reduction, data presentation, and data verification as well as checking the validity of the data. The results showed that the application of the experimental method in learning science about the photosynthetic material had been carried out several stages, namely: the preparation stage, the implementation stage, and the closing stage. In the preparation phase, the teacher must convey the learning objectives to be achieved. Furthermore, the implementation stage contains an explanation of the material, a demonstration of performance, and photosynthesis observation activities on botanical plants. Finally, the concluding stage contains a repeat of photosynthetic observations of the students that are carried out on botanical plants. There are several obstacles that are found in the application of experimental methods in learning science in SDN Inpres Bumi Bahari, namely: lack of students' attention to the experimental method in learning science, material about photosynthesis in the classroom. The way that can be taken to solve this problem is to invite students to work together in the learning process in the classroom so that students can easily capture and understand the lessons explained by the teacher. This can be done by the teacher to students so that students easily understand and comprehend the learning given and explained by the teacher